SYNTHETIC JET MICROPUMP - Abdou, Sherif (My University, 2014)
The production of a novel micropump based on the synthetic jet principle is investigated both numerically and experimentally. The proposed micropump consists of a synthetic jet actuator driven by a vibrating diaphragm issuing into an inverted T- shaped channel structure forming the inlet/outlet channels of the pump.
The software package Ansys is used to perform numerical investigations of the operation of the proposed micropump. Simulations were performed to study the effect of changing the inlet/outlet channel dimensions as well as the operating frequency, amplitude and duty cycle of the excitation signal. Inlet/outlet channel widths ranging from 200 to 800 μm and operating amplitude and frequency of excitation of the 5 mm square membrane driving the synthetic jet actuator ranging from 20 to 60 μm and from 20 to 60 Hz respectively were investigated.
Based on the findings of the numerical simulations, a prototype design was chosen and produced. Prototype production using microfabrication techniques as well as micromachining was investigated. The final prototype was micromachined using plexiglass as the working material. An experimental setup was constructed to test the performance of the produced prototype, which allowed for measuring the produced flow rate, pressure head, actuation amplitude and frequency.
The findings of the numerical simulations verified the possibility to produce a working micropump with flow rates of up to 1.3 ml/min. Simulation results also showed the dependence of the produced flow rate on both the inlet and outlet channel widths. An increase in the inlet channel width resulted in a gain in the average flow rate through the pump while an increase in the outlet channel width results in a reduction in the flow rate. Increases in either the actuation amplitude or frequency of excitation both resulted in an improvement in the produced flow rate. Changes in the ejection duty cycle, or the ejection time relative to the suction time during an actuation cycle, were found to influence the flow rate produced by the pump. A shorter ejection time produced a higher flow rate from the pump as compared to a longer ejection time. It was also found that changes in dimensions or operating parameters affected the fluctuations in the flow rate through the pump associated with the pulsating nature of the synthetic jet. Experimental investigations confirmed the findings of the numerical simulations in terms of the flow rate and the trends in the dependence of the flow rate on operating parameters. Values of maximum back pressure of up to 500 Pa were also reported experimentally and membrane driving powers of up to 122 μW were calculated numerically.
Keywords: MEMS; Microfluidics; Micropump; Synthetic Jet; Micro Synthetic Jet; Electro-Mechanical Systems; Nanoscience and Nanotechnology; Electro-Mechanical Systems